Confounding changes in averages with marginal effects: How anchoring can destroy economic value in strategic investment assessments - Shapira, Zur; Shaver, J. Myles (Strategic Management Journal, 2014)
Profit maximization requires that decision makers assess marginal profits. We demonstrate that decision makers often confound marginal profits with changes in average profits (e.g., changes in return‐on‐investment). This results in systematic deviations from profit maximization where decision makers forgo profit‐enhancing investments that reduce average profits or engage in loss‐enhancing investments that decrease average losses. In other words, average profit becomes an anchor by which new investments are assessed. We conduct two decision‐making experiments that show this bias and demonstrate it is pronounced when average profit data are accessible or task‐relevant. Moreover, we find within‐subject effects across experiments, which helps demonstrate the mechanism that invokes the bias . Copyright © 2013 John Wiley & Sons, Ltd.